Hubungan Tingkat Stres Akademik dengan Siklus Menstruasi pada Mahasiswi Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh - Rinella Wihandi, Fadira; Nadira, Cut Sidrah; Yudhi Iqbal, Teuku (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2023)
College students are a group that is prone to stress. Heavy lecture loads and quite a lot of exams are often the cause of high levels of stress in medical students. Stress can increase the release of Corticotropin Releasing Hormone (CRH) from the Hypothalamic-Pitutary-Adrenal (HPA) which in turn can affect an important hormone in reproductive function, namely Gonadotropin Releasing Hormone (GnRH). The purpose of this study was to determine the relationship between academic stress levels and the menstrual cycle of female students at the Malikussaleh University Medical Study Program. This type of research is an observational analytic study using a cross sectional design. In this study, probability sampling technique was used with stratified random sampling for the sampling technique. The study sample size was 168 respondents who met the inclusion and exclusion criteria. The data used in this study is primary data obtained by distributing questionnaires to respondents. The research data were analyzed using the Spearman rank test. The results of the study showed respondents with abnormal menstrual cycles, the majority were owned by respondents with severe and very heavy levels of academic stress. The conclusion of this study is that there is a significant relationship between academic stress levels and the menstrual cycle of female students of the Malikussaleh University Medical Study Program.